(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Electronic tools have given rise to the production and growth of the e-publishing industry in the area of ICT. Digital content resides in a medium that can be stored, structured, distributed and viewed by a device without any transfer method interfering. They refer to the use of information technology in the development of publications and the dissemination of text via electronic means through computer terminals. The aim of the collection development is to recognize the knowledge needs of consumers, pick, obtain valuable records, follow a comprehensive and judicious expenditure on document selection, check the selection regularly and weed out unnecessary materials from the collections. It was aimed at creating a diverse collection that satisfies the university library’s priorities. This paper covers the theoretical description of collection development and electronic information resources developing perspectives of Collection Management Functions.